The necessity of creation the new economic mechanism due to development of corporate social responsibility’s programs; Проблемы управления рыночной экономикой; Т. 1 - Khaperskaya A. V. Alena Vasilievna (Менеджмент, 2015)
Заглавие с титульного экрана